Barriers to price convergence - Glushenkova, Marina; Kourtellos, Andros; Zachariadis, Marios (Wiley, 2018)
This paper uncovers novel empirical patterns in the cross-country price mechanism using a nonlinear factor model and threshold regression analysis based on individual goods retail price data for a large panel of countries. To our knowledge, this is the first paper to find strong evidence for club convergence of retail prices. These clubs emerge due to the interaction of traded and non-traded factors. For example, countries physically closer to potential trade partners converge faster than countries in the high distance regime as long as they have low initial labor productivity or low initial income. Moreover, we find an asymmetry in the extent that arbitrage opportunities related to international trade are exploited, with low initial price regime countries exhibiting faster convergence from below than high initial price regime countries exhibit from above, consistent with less resistance to exporting than to importing due to political economy considerations. We interpret our findings as evidence of a local law of one price due to barriers to price convergence influencing the duration of the effect of price shocks.